Analysis of risks in investment projects - Mammadova, К. M.; Agayev, І.; Мамедова, К. М.; Агаєв, І. Д. (Харківський національний автомобільно-дорожній університет, 2025)
Financial modeling, budgeting, risk assessment, and investment project management strategies are essential tools for the successful implementation of projects. These approaches are crucial for accurately evaluating the financial outcomes of investment projects, mitigating potential risks, and making effective decisions. Since each project has its unique characteristics, the application of methods in these areas can vary depending on the specific requirements of the project. The article provides a comprehensive analysis of the primary methods for risk analysis in investment projects, discussing the types of risks, their assessment, management, and impact on project success. Risk assessment is a key element in ensuring the financial stability and long-term effectiveness of investment projects. The major categories of risks in the financial sector are identified, including market, credit, liquidity, operational, legal, regulatory, and reputational risks. Specific management methods are proposed for each category, including diversification, hedging, insurance, and internal control mechanisms. Particular attention is given to modern risk management methods, such as Value-at-Risk (VaR), the Monte Carlo method, scenario analysis, and sensitivity analysis, which allow for more precise risk evaluation and forecasting, especially in unstable markets and during economic fluctuations. Market and operational risks, which arise from price changes, exchange rates, or business process errors, can significantly impact the financial stability of organizations. The importance of financial modeling and budgeting for making well-grounded decisions is also emphasized. The consideration of new challenges, such as cyber threats and environmental factors, promotes the integration of ESG criteria into investment decision-making processes. Overall, effective risk management is crucial for ensuring the stability and success of investment projects amid global transformations.
Аналіз ризиків в інвестиційних проєктах
Keywords: investor; risk analysis; investment project; market conditions; operational processes; technological changes; інвестор; аналіз ризиків; інвестиційний проєкт; ринкові умови; операційні процеси; технологічні зміни; 338.14; 10.30977/ЕТК.2225-2304.2025.45.139